(untitled) (Medicine Today, 2021)
Introduction: This retrospective study was done to see colonoscopic yields in patients presenting with lower gastrointestinal bleeding. Materials & Methods: Reports of patients undergoing colonoscopy due to bleeding per rectum were retrieved from endoscopy records. Patients’ particulars and colonoscopic findings were recorded in a data sheet. Analysis was done using SPSS 20 version. Results: A total of 309 patients (male 211 (68.3%) and female 98 (31.7) with mean age 40.3 years %)) were included in this study. According to colonoscopic yield, causes of LGIB were haemorrhoids 137 (44.33% ), rectal and colonic growth 58(18.77% ) rectal and colonic polyps 54 (17.47% ), anal fissure 38 (12.29% ), proctitis 18 (5.82%), colitis 18(5.82%), ileal ulcer and ileitis 34(11.0%). Colorectal growth was more common among patients age 26 to 60years. Among male rectal growth was slightly higher than female. Conclusion: Lower gastrointestinal bleeding is more common among males. Commonest cause of LGIB are internal haemorrhoids, rectal growth, rectal and colonic polyps and anal fissure. Colorectal neoplasm, proctitis, colitis and ileal inflammation and ulcers constitute small part. Medicine Today 2021 Vol.33(2): 120-122